Pelatihan: Evaluasi dan Rekonstruksi Kinerja ASN Pemerintah Kota Kupang Berbasis Sumber Daya Manusia - Jefirstson Richset Riwukore (Yumary: Jurnal Pengabdian kepada Masyarakat, 2022)
Purpose: The provision of community service activities aims to provide knowledge, understanding, and skills to state civil servants related to the ability to evaluate and reconstruct the performance of ASN based on human resources by organizational needs and existing conditions. Methodology/approach: Implementing activities using focus group discussions and workshops with the following stages: (1) surveys to find out partner problems, (2) needs analysis and initial questionnaire distribution using purposive sampling and quota sampling methods; (3) training and design consist of sharing information and materials, training on evaluation techniques, and training on reconstruction techniques; (4) the distribution of the final questionnaire to determine the increase in knowledge of participants' skills related to evaluation and reconstruction methods; and (5) prepare reports. Analysis of human resource-based ASN performance reconstruction using factorial analysis of SPSS vs. 25 Results/findings: The results of evaluating the performance of ASN based on human resources identified 33 dimensions of employee performance based on existing human resources. After being reconstructed into 9 dimensions of ASN performance based on human resources, namely professional, target, credible, teamwork, focus, capability, innovative, infrastructure, and perfectionist. Conclusion: The results of this training show that there is an increase in the knowledge and skills of ASN in the Kupang City Government to evaluate and reconstruct the elements of human resource-based performance appraisal and measurement that are in accordance with existing conditions and organizational needs.